2006
DOI: 10.2320/matertrans.47.1864
|View full text |Cite
|
Sign up to set email alerts
|

Copper Enrichment of Iron-Base Alloy Scraps by Phase Separation in Liquid Fe-Cu-P and Fe-Cu-P-C Systems

Abstract: A clear phase separation into liquid iron-rich and copper-rich alloys was observed when a mixture of Fe, Cu and P was melted in an alumina or carbon crucible at 1373 K. Since this phase separation is considered to be useful for recovering valuable copper from iron-base alloy scraps, the phase equilibrium in the Fe-Cu-P and Fe-Cu-P-C systems was investigated in this study. The effect of carbon to the phase separation was determined in the concentration range of phosphorous between 7 and 11 mass% at 1373 K. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The augmented mixing entropy displays an increased level of disorder and superior miscibility, as showcased by the more uniformly dispersed Fe-rich regions on the Cu-rich matrix depicted in Figure 2c. Based on previous research, it has been found that elements C and B widen the miscibility gap between Fe and Cu, as shown in Figure 10b [42,43]. This extended duration of the melt pool within the immiscible gap facilitates liquid phase separation [44,45].…”
Section: Cumentioning
confidence: 82%
“…The augmented mixing entropy displays an increased level of disorder and superior miscibility, as showcased by the more uniformly dispersed Fe-rich regions on the Cu-rich matrix depicted in Figure 2c. Based on previous research, it has been found that elements C and B widen the miscibility gap between Fe and Cu, as shown in Figure 10b [42,43]. This extended duration of the melt pool within the immiscible gap facilitates liquid phase separation [44,45].…”
Section: Cumentioning
confidence: 82%
“…The binary melt of iron and copper is a miscible composition at high temperatures (Massalski & Okamoto, 2000), and the addition of carbon or phosphorus to the binary melt leads to a phase separation into liquid iron-rich and copper-rich phases (Hino, Washizu, & Nagasaka, 1998). The copper phase can generally absorb some precious metals such as gold and palladium (Yamaguchi et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Sun et al [ 11 ] developed a new kind of matrix containing up to 2.0 vol.% of randomly dispersed SiC whiskers. As shown in [ 12 , 13 , 14 ], obtaining the desired mechanical and tribological properties is also possible through modification with alloy powders, which can effectively overcome the problems of component segregation, uneven element distribution, low alloying and diamond thermal damage. Shi et al [ 15 ] investigated the influence of alloying on Fe-Cu based metal matrix composites.…”
Section: Introductionmentioning
confidence: 99%